2016
DOI: 10.1038/mt.2016.120
|View full text |Cite|
|
Sign up to set email alerts
|

Inducible HGF-secreting Human Umbilical Cord Blood-derived MSCs Produced via TALEN-mediated Genome Editing Promoted Angiogenesis

Abstract: Mesenchymal stem cells (MSCs) promote therapeutic angiogenesis to cure serious vascular disorders. However, their survival period and cytokine-secretory capacity are limited. Although hepatocyte growth factor (HGF) can accelerate the rate of angiogenesis, recombinant HGF is limited because of its very short half-life (<3–5 minutes). Thus, continuous treatment with HGF is required to obtain an effective therapeutic response. To overcome these limitations, we produced genome-edited MSCs that secreted HGF upon dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 32 publications
2
43
0
Order By: Relevance
“…In order to overcome these limitations, guided nucleases can be used. In the context of MSCs secretome modification, we were able to find the only article where HGF-secreting MSCs were obtained by TALEN-mediated genome editing [64]. In the present article, we applied another type of guided nucleases, CRISPR/Cas9, that is characterized by target design simplicity and possibility of multiplex gene expression regulation compared to TALENs and ZFNs [65].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to overcome these limitations, guided nucleases can be used. In the context of MSCs secretome modification, we were able to find the only article where HGF-secreting MSCs were obtained by TALEN-mediated genome editing [64]. In the present article, we applied another type of guided nucleases, CRISPR/Cas9, that is characterized by target design simplicity and possibility of multiplex gene expression regulation compared to TALENs and ZFNs [65].…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, Flt-1-engineered MSCs caused regression of endometriotic lesions [50]. A plenty of other fascinating results are obtained by applying MSCs with genetically modified paracrine activity [57,58,63,64]. However, in the vast majority of studies, the gain-of-function genetic perturbations are obtained by the use of cDNA overexpression systems.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregates were also shown to reduce the fibrotic areas in the ischemic limb tissues of mice because of their bulkiness and effective entrapment at the transplantation sites (6). Combination therapies such as microgels with gene modifications or spheroids with low-level light have also been developed to enhance angiogenesis in the context of animal models of limb ischemia (12, 32). …”
Section: Modified Methods For Enhancing Angiogenesismentioning
confidence: 99%
“…Clinical interest has been focused on therapeutic angiogenesis by injecting ex vivo expanded LEPCs into patients. Various clinical studies have shown improved vascular outcomes in patients with ischemic and chronic wounds . However, one of the major challenges for this approach is that a low number of intravenously injected LEPCs reach the site of diseased target area due to their circulatory nature and low adhesion rate .…”
mentioning
confidence: 99%
“…Clinical interest has been focused on therapeutic angiogenesis by injecting ex vivo expanded LEPCs into patients. Various clinical studies have shown improved vascular outcomes in patients with ischemic and chronic wounds [2,6]. However, one of the major challenges for this approach is that a low number of intravenously injected LEPCs reach the site of diseased target area due to their circulatory nature and low adhesion rate Abbreviations BST2, bone marrow stromal cell antigen 2; ECD, extracellular domain; ECs, Endothelial cells; HUVECs, human umbilical vein endothelial cells; IFN-c, Interferon gamma; LEPCs, Late endothelial progenitor cells.…”
mentioning
confidence: 99%